Hollow sandwich-structured N-doped carbon-silica-carbon nanocomposite anode materials for Li ion batteries. (April 2020) - Tang, Xinde; Zhao, Chunli; Li, Zhanfeng; Zhang, Yipin; Gu, Shaonan
Abstract: Silica has attracted much attention as a promising anode material for lithium ion batteries (LIBs), however, the low conductivity and unstable solid electrolyte interface (SEI) film limit its applications. In this paper, hollow sandwich-structured N-doped carbon-silica-carbon (CSC) nanoparticles was designed and prepared as anode materials for LIBs. The combination of polymer template approach and dopamine self-oxidation polymerization results in the conformal coatings on the surface of silica, which enhances the conductivity and stability of the composite materials. The hollow sandwich-structured material displays a high reversible capacity of 480 mA h g-1 at current density of 1.0 A g-1 and excellent rate performance, which can be attributed to the synergetic effect of the unique structure of hollow silica and N-doped carbon conformal coatings. The hollow sandwich-structured N-doped carbon-silica-carbon composite materials can be promising anode materials for LIBs.